Metode AHP dalam Sistem Pendukung Keputusan pada Pemilihan Website Penerbangan Online - Maysaroh, Maysaroh; Fahmi, Muhammad; Destiana, Henny; Maulana, Yana Iqbal; Komarudin, Ishak (LPPM Universitas Nusa Mandiri, 2022)
At the moment transportation services are needed a lot, be it land, sea or air transportation. Supported by Information Technology, it adds to the competition between online ticket sales service companies in carrying out their sales promotions. The transportation service business is required to be able to provide the best possible services, offers and promotions in order to compete with other online transportation service bureaus in attracting consumers. Competition between online companies or travel agents is very competitive, with competition, a study was made to test which online flight website sites are most in demand by consumers today, 4 online flight sites were taken for this research, namely Tiket.com, Traveloka, Pegi-pegi .com and Nusatrip. By using the Analytical Hierarchy Process method or better known as AHP. The AHP method was chosen because it can select the best alternative from a number of alternative choices based on predetermined criteria. so that later this research will make it easier for consumers to decide in choosing the best online flight website or the most in demand. In addition, the AHP method is one of the most relevant methods and has a consistency value calculation in determining the priority level of the selection criteria. From the test results, it is found that the Traveloka website has a very high value with the value of Traveloka (0.49), Tiket.com (0.22), Pegipegi.com (0.19), and Nusatrip (0.11).